Manajemen Strategi Komunitas Compok Literasi Dalam Membangun Budaya Literasi - Ghazali, Ziyadul Ifdhal; Ifadhah, Hurriyatul; Fakhiroh, Eva Zakiyatul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The Compok Literacy Community is a youth-driven platform designed to facilitate collaboration, knowledge sharing, and collective problem-solving in educational and social contexts. The core problem addressed in this study is the low reading interest among children and youth, which necessitates innovative and community-based strategies to cultivate a sustainable literacy culture. The aim of this research is to analyze the management strategies employed by the Compok Literacy Community in fostering such a culture. This study employs a qualitative descriptive approach within the field research framework. Participants include the community's founders, managers, and volunteers. Data collection techniques consist of interviews, observation, and documentation, while data analysis follows the stages of data reduction, verification, and conclusion drawing. The findings indicate that (1) the development of a literacy culture within the community stems from the founders’ strong commitment to promoting reading interest and establishing a literacy-rich environment; (2) the implementation strategies include initiating the community with close personal networks, recruiting motivated volunteers, assigning tasks based on individual potentials, and designing continuous, literacy-based programs; and (3) these strategies significantly impact not only the volunteers but also the surrounding community and local schools. This research contributes to the field of educational management by providing a practical model of grassroots literacy promotion through effective community-based management strategies. The findings demonstrate that strategic and inclusive management can lead to a sustainable culture of literacy and empower young people to become active agents of educational change.